SUPLEMENTASI KULTUR Saccharomyces spp.G-7 SEBAGAI SUMBER PROBIOTIK DALAM RANSUM BASAL TERHADAP PENAMPILAN BROILER UMUR 2-6 MINGGU - N. K. N., Mahartini; Bidura, I G. N. G.; Utami, I. A. P. (Jurnal Peternakan Tropika; Vol 2 No 1 (2014), 2014)
The aim of this study is to obtain the optimum level of supplementation of Saccharomyces spp.G-7 culture as a source of probiotics in the ration against performance of broilers aged 2-6 weeks. About 36 chickens were chosen in average 2 week old broiler chickens with homogeneous weight, without considering the sex of the chickens. Complete randomized design (CRD) method used with three treatments and six repetitions. The third treatment was chicken which were given basal rations without supplementation of cultures of Saccharomyces spp.G-7 as a control (A), with 0,20% supplementation of cultures of Saccharomyces spp.G-7 (B), and 0.40% supplementation of cultures of Saccharomyces spp . G-7 ( C). Each experimental unit were filled with two of 2 weeks of age broiler chickens with homogeneous weight. Variables which were observed including: ration consumption, water consumption, final body weight, weight gain, "Feed Conversion Ratio" (FCR). Based on the results above that supplementation of cultures of Saccharomyces spp.G-7 at the level of 0,20% and 0,40% in the basal diet (P<0.05) was obviously increased the feed consumption, water consumption, final body weight, weight gain , and efficiency of feed utilization compared to control. It is concluded that supplementation of 0,20% Saccharomyces spp.G-7 culture as a source of probiotics in diets were increased performance of broiler aged 2-6 week.
Keywords: Probiotics, Saccharomyces spp G-7, performance, broiler